2016
DOI: 10.1007/s12011-015-0587-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Organic Forms of Zinc, Selenium and Chromium on Performance, Anti-Oxidant and Immune Responses in Broiler Chicken Reared in Tropical Summer

Abstract: Two experiments were conducted to study the effect of supplementing organic forms of zinc (Zn), selenium (Se) and chromium (Cr) on performance, anti-oxidant activities and immune responses in broiler chickens from 1 to 21 days of age, which were reared in cyclic heat-stressed condition under tropical summer in open-sided poultry house. A total of 200 (experiment I) and 450-day-old (experiment II) broiler male chicks (Cobb 400) were randomly distributed in stainless steel battery brooders (610 mm × 762 mm × 475… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 47 publications
11
50
0
3
Order By: Relevance
“…For example, adding a combination of zinc and vitamin C in the diet of layer hens decreased the negative impact of both cold and heat stress, thus, there were an improvement in egg production compared to the control group (Gerzilov et al, 2015). Rao et al (2016) reported that supplementation of 40 mg/kg Zn significantly improved growth performance and anti-oxidant responses of broiler male chicks exposed to heat stress during 1-21 days of age. Sunder et al (2008) showed that addition of zinc to broiler diets was important for improving immune response and mineral retention.…”
Section: Mode Of Action Of Zinc In Poultry Nutritionmentioning
confidence: 99%
“…For example, adding a combination of zinc and vitamin C in the diet of layer hens decreased the negative impact of both cold and heat stress, thus, there were an improvement in egg production compared to the control group (Gerzilov et al, 2015). Rao et al (2016) reported that supplementation of 40 mg/kg Zn significantly improved growth performance and anti-oxidant responses of broiler male chicks exposed to heat stress during 1-21 days of age. Sunder et al (2008) showed that addition of zinc to broiler diets was important for improving immune response and mineral retention.…”
Section: Mode Of Action Of Zinc In Poultry Nutritionmentioning
confidence: 99%
“…Показано (9,10), что введение в рацион цыплят-бройлеров наночастиц хрома в дозировках 100-200 мкг/кг стимулирует обмен химических элементов. Существует противоположное мнение (11)(12)(13)(14) о том, что хром может оказывать отрицательное воздействие на организм. Поскольку реакция на определенное количество тяжелого металла разная, при введении в рацион хрома в дозировках 100 мкг/кг происходит как стимуляция, так и торможение некоторых процессов, которые напрямую зависят от его количества в корме.…”
unclassified
“…The Cu-ZnSOD, in which Zn is an integral part, is an important antioxidant defense in nearly all living cells exposed to oxygen (Paz Matias et al 2014). Rao et al (2016) found that supplementation of organic form of Zn increased SOD. Similarly, the results from our study also indicated that Zn supplementation increased the activity of Cu-ZnSOD.…”
Section: Discussionmentioning
confidence: 99%